Du mysticisme au nationalisme religieux : les ambiguïtés de Sâmiha Ayverdi (1905-1993) - Laurent Mignon (European Journal of Turkish Studies)
The present article questions the apparent contradictions in the work of Samiha Ayverdi (1905-1993), the novelist and disciple of Kenan Rifai (1867-1950). Her novels and poetic prose chant a universalist mystical love, giving women a special place as actresses of the mystical quest, often outside the norms of the conservative bourgeoisie, as in the novel Son Menzil [The Final Stage, 1943], studied here. However, it is possible to speak of a break in Ayverdi’s intellectual journey from the moment she succeeded Rifai as head of the Istanbul branch of the Rifaiyye, which had been reformed into a cultural circle. Her literary writings gave way to autobiographical texts and columns that promoted religious nationalism with strong xenophobic, anti-Semitic and anti-communist tones. These can be read as an attempt at counter-history celebrating Ottoman history and culture in response to its detractors in the Kemalist camp and the West.